2020
DOI: 10.1093/ejcts/ezaa038
|View full text |Cite
|
Sign up to set email alerts
|

Detrimental effects of cerebrospinal fluid pressure elevation on spinal cord perfusion: first-time direct detection in a large animal model

Abstract: OBJECTIVES Cerebrospinal fluid (CSF) drainage is routinely utilized to mitigate perioperative and postoperative spinal cord ischaemia in open and endovascular thoraco-abdominal aortic aneurysm repair to prevent permanent paraplegia. Clinical decision-making in the vulnerable perioperative period, however, is still based on limited clinical and experimental data. Our aim was to investigate the isolated effect of CSF pressure elevation on spinal cord perfusion in an established large animal mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The changes observed on MRI may not correlate with clinical findings at follow-up 9 . MRI to date remains the gold standard for the diagnosis of SPAM; however, the use of computed tomography scan 8 , Cerebrospinal fluid (CSF) examination 2,6,8,24 , lumbar puncture 2,6,8,24 , myelography 2,28 , and selective spinal angiography 6,9 have been reported.…”
Section: Radiological Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…The changes observed on MRI may not correlate with clinical findings at follow-up 9 . MRI to date remains the gold standard for the diagnosis of SPAM; however, the use of computed tomography scan 8 , Cerebrospinal fluid (CSF) examination 2,6,8,24 , lumbar puncture 2,6,8,24 , myelography 2,28 , and selective spinal angiography 6,9 have been reported.…”
Section: Radiological Evaluationmentioning
confidence: 99%
“…Surgical decompression was performed to reduce the increased CSF pressure with an attempt at SPAM resolution in 2 cases in accordance with the CSF flow alteration hypothesis in SPAM 12,18 . Yablon et al 28 suggested early surgical decompression after the initial SCI could prevent SPAM. Okada et al 14 proposed laminectomy with a pial incision.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…2 As SCI entails devastation, laboratory and animal research aimed at developing strategies to control its risks is ongoing. 3,4 Neurophysiological monitoring has obviously received much attention for some 3 decades now, and much research has been devoted to identifying the ideal monitoring system, which theoretically should be able to identify ischemia in the shortest period and recognize the efficacy of reperfusion after surgical maneuvering. Transcranial motor-evoked potential (TC-MEP) monitoring is currently the most reliable technique in the clinical setting and provides more rapid information during ischemia and fewer false-positive results for reperfusion compared with somatosensory evoked potentials (SSEPs).…”
mentioning
confidence: 99%
“… 2 As SCI entails devastation, laboratory and animal research aimed at developing strategies to control its risks is ongoing. 3 , 4 …”
mentioning
confidence: 99%